ROOT ABSORPTION AS A METHOD OF INTRODUCING INSECUCIDES INTO COCONUT PALMS FOR THE CONTROL OF LEAF FEEDING CATERPILLARS - Christa Ulin Ginting; R. Desmier de Chenon (International Coconut Community, 1987)
The root absorption technique has been shown to be very effective method for the control of coconut leef feeding caterpillars. However, this method, in order to be effective, requires a good system for monitoring the population level of the pest and a well organized and coordinated pest control teams. Like the trunk injection method the root absorption technique has also many advantages: high effectiveness, good distribution of insecticides in the leaves, efficient, less harmful, long remanence does not affect the natural enen‑des, thus a good method to use for integrated pest control. Furthermore, unlike the trunk injection method, the root absorption technique utilizes the root, not the trunk, of the coconut palm for introducing the pesticide. Hence, not injurious to the tree as well.